1998
DOI: 10.1038/sj.bjp.0702124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DMPPO, a phosphodiesterase type 5 inhibitor, on hypoxic pulmonary hypertension in rats

Abstract: 1 Cyclic guanosine 3' ± 5'-monophosphate (cyclic GMP) is the second messenger of important physiologically active mediators controlling the pulmonary vascular tone. To potentiate the e ects of cyclic GMP on the pulmonary vasculature, we used DMPPO, a new selective PDE-5 inhibitor, and examined its action in a rat model of hypoxic pulmonary hypertension. 2 Levels of cyclic GMP measured during baseline conditions at 5 and 60 min of perfusion were similar in the perfusate of isolated lungs from normoxic and chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
(34 reference statements)
1
11
1
1
Order By: Relevance
“…However, these results are at odds with previously published observations from our laboratory and others demonstrating no significant effect of CH on vasodilatory responsiveness to NO-donors (26) or inhaled NO (25,8) in isolated lungs from male rats. Furthermore, Isaacson et al (12) reported that CH enhanced vasodilatory responses to arterial boluses of saturated NO solution in isolated lungs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, these results are at odds with previously published observations from our laboratory and others demonstrating no significant effect of CH on vasodilatory responsiveness to NO-donors (26) or inhaled NO (25,8) in isolated lungs from male rats. Furthermore, Isaacson et al (12) reported that CH enhanced vasodilatory responses to arterial boluses of saturated NO solution in isolated lungs.…”
Section: Discussioncontrasting
confidence: 99%
“…Levels of cGMP are further regulated by the rate of degradation by cGMP-specific phosphodiesterase type 5 (PDE5), which plays a significant role in modulating pulmonary VSM tone (5,6,8,13,21,40). Once formed, cGMP can mediate VSM relaxation through several mechanisms involving a decrease in intracellular calcium and/or decreased sensitivity of the contractile apparatus to calcium (17).…”
mentioning
confidence: 99%
“…29) Other PDE5 inhibitors also have pulmonary selectivity in the model of PH. 30,31) These observations support that selective PDE5 inhibitors such as T-1032 show pulmonary selectivity in PH. When we determined the pulmonary selectivity using RVSP and MAP, other hemodynamic changes such as cardiac output and contraction should be considered, because these parameters influence RVSP.…”
Section: Discussionsupporting
confidence: 53%
“…This pathophysiological adaptation of the pulmonary circulation to maintain hypoxia is a complicated process for which no curative treatment, except heart -lung transplantation, is currently available. Since PDEs are present in the pulmonary artery wall (Rabe et al, 1994;Maclean et al, 1997) and that cGMP-PDE activity is mainly because of the action of PDE5 (Rabe et al, 1994), some PDE5 inhibitors have been administered to counteract PAHT development both in animals and human (Eddahibi et al, 1998;Ziegler et al, 1998;Hanasato et al, 1999). Very recently, pioneer clinical trials with sildenafil have been performed in PAHT (Abrams et al, 2000;Ichinose et al, 2001;Zhao et al, 2001).…”
Section: Introductionmentioning
confidence: 99%